Boosted objects and jet substructure at the LHC. Report of BOOST2012, held at IFIC Valencia, 23rd-27th of July 2012 - Altheimer, A.; Arce, A.; Asquith, L.; Mayes, J. Backus; Kuutmann, E. Bergeaas; Berger, J.; Bjergaard, D.; Bryngemark, L.; Buckley, A.; Butterworth, J.; Cacciari, M.; Campanelli, M.; et al. (Springer, 2014)
This report of the BOOST2012 workshop presents the results of four working groups that studied key aspects of jet substructure. We discuss the potential of first-principle QCD calculations to yield a precise description of the substructure of jets and study the accuracy of state-of-the-art Monte Carlo tools. Limitations of the experiments' ability to resolve substructure are evaluated, with a focus on the impact of additional (pile-up) proton proton collisions on jet substructure performance in future LHC operating scenarios. A final section summarizes the lessons learnt from jet substructure analyses in searches for new physics in the production of boosted top quarks.